Comparing Horizontal and Vertical Surfaces for a Collaborative Design Task. (17th April 2012) - Potvin, Brianna; Swindells, Colin; Tory, Melanie; Storey, Margaret-Anne
Abstract : We investigate the use of different surface orientations for collaborative design tasks. Specifically, we compare horizontal and vertical surface orientations used by dyads performing a collaborative design task while standing. We investigate how the display orientation influences group participation including face-to-face contact, total discussion, and equality of physical and verbal participation among participants. Our results suggest that vertical displays better support face-to-face contact whereas side-by-side arrangements encourage more discussion. However, display orientation has little impact on equality of verbal and physical participation, and users do not consistently prefer one orientation over the other. Based on our findings, we suggest that further investigation into the differences between horizontal and vertical orientations is warranted.